Design and fabrication of power hacksaw project / Joshua Aji Stephen - Stephen, Joshua Aji (2024)
Power hacksaws play an important part in industry nowadays, with the help of external power such as electric motor and hydraulic power source. In this project, the problem statement is that the manual hacksaw requires a lot of effort and causes fatigue toward the operator. Also, the existing power hacksaw is too expensive in the market. Other than that, the objective of this project is to design a power hacksaw which will lessen the effort to be use and not too expensive but can still function as power hacksaw. Last but not least, the expected result is that it will be less expensive, easy to use and can handle heavy-duty materials because it uses external power such as electric motor. With the result of this design, it can reduce the effort needed to cut things, especially thick metals